Lidocaine Nerve Block Diminishes the Effects of Therapeutic Electrical Stimulation to Enhance Nerve Regeneration in Rats. (January 2023) - Keane, Grace C.; Marsh, Evan B.; Hunter, Daniel A.; Schellhardt, Lauren; Walker, Eric R.; Wood, Matthew D.
Background: Although electrical stimulation (ES) can improve nerve regeneration, the impact of nerve block, such as lidocaine (Lido), on the therapeutic benefits of ES remains unclear. We used a rat tibial nerve transection-and-repair model to explore how either preoperative (PreOp) or postoperative (PostOp) nerve block affects ES-related improvement in regeneration. Methods: Lewis rats were used in 1 of 2 studies. The first evaluated the effects of extraneural Lido on both healthy and injured nerves. In the second study, rats were randomized to 5 experimental groups: No ES (negative control), PreOp Lido, ES + PreOp Lido, PostOp + ES, and ES (positive control). All groups underwent tibial nerve transection and repair. In both studies, nerves were harvested for histological analysis of regeneration distal to the injury site. Results: Application of extraneural Lido did not damage healthy or injured nerve based on qualitative histological observations. In the context of nerve transection and repair, the ES group exhibited improved axon regeneration at 21 days measured by the total number of myelinated fibers compared with No ES. Fiber density and percentage of neural tissue in the ES group were greater than those in both No ES and PreOp Lido + ES groups. ES + PostOp Lido was not different from No ES or ES group. Conclusions: Extraneural application of Lido did not damage nerves. Electrical stimulation augmented nerve regeneration, but Lido diminished the ES-related improvement in nerve regeneration. Clinical studies on the effects of ES to nerve regeneration may need to consider nerve block as a variable affecting ES outcome.